Implementation of RIO in UMJaNetSim / Chan Chin We - Chan, Chin We (2004)
As the complexity and diversity of network have grown, network simulator has proven to be an important tool in the design, analysis, testing and performance estimation of network. Besides that, network simulator can also perform a variety of functionalities such as network planning, network monitoring, protocol analyzer and so forth. In this project, I will do some research on the recent TCP congestion control and avoidance mechanisms and implement one of the mechanisms into the Java Network Simulator (JaNetSim). The current version of JaNetSim has been implemented RED congestion avoidance mechanism. Therefore, this project will focus on the RIO (RED with in and out profile) queue mechanism. RIO, initially proposed in the context of Differtiated Services networks by distinguish between two classes of packets - in-profile and out-of-profile, which is based on the marking scheme. Besides that, various marking scheme have also been proposed. In this project, I will focus on the earliest making algorithm, which is calculating the average queue sizes for in-profile packets and total packets. Traditionally, packet marking is performed by ingress routers according to a user-profile specified in term of bandwidth.